Electrical Conductivity of Polyaniline Fiber Synthesized by Interfacial Polymerization and Electrospinning - Ngurah Ayu Ketut Umiati; Kamsul Abraha; Kuwat Triyana (Institute of Advanced Engineering and Science, 2017)
Polyaniline fiber is a promising biosensor material due to the capability of this material as an effective mediator for electron transfer. The polyaniline in fibre has wider surface to increase the electron transfer. In this work, polyaniline structure synthesized by interfacial polymerization was compared to polyaniline structure obtained from electrospinning to get a better fibre structure. Interfacial polymerization was carried out to form a polymerization between the water phase and the organic phase. The water phase was prepared from dopants, initiator and aquadestilata and the organic phase was was made from toluene as an organic solvent and aniline monomer. Electrospinning was conducted by using a dc high voltage 15 kV and 0.5 mm syringe needle to produce fibers from a melt polymer solution taken from interfacial polymerization. The scanning electro microscope results confimed the formation of polyaniline in structure of fiber. Resistance measurement by using LCR meter showed that polyaniline fiber resulted from electrospinning is more conductive than polyaniline fiber formed by interfacial polymerization method.